Ink based on poly(3,4-ethylene dioxythiophene), poly(sulfonostyrene) and silver nanoparticles (PEDOT/PSS/SNP) blends for fabrics printing - Ahmad Shahrim, Nur’Aishah; Mohd Hafiz, Nur Nadia; Ahmad, Zuraida; Wong Azman, Amelia; Buys, Yose Fachmi; Sarifuddin, Norshahida (Industrial Chemistry Research Institute, 2022)
The influence of co-solvents such as: dimethylsulfoxide (DMSO), isopropyl alcohol (IPA), ethylene glycol (EG), ethanol (EtOH) and deionized water (DI) on the properties of ink based on poly(3,4- -ethylene dioxythiophene), poly(sulfonostyrene) and silver nanoparticles (PEDOT/PSS/SNP) blends was investigated. The ink was obtained by the ultrasonic dispersion method by mixing PEDOT, PSS and SNP and then adding co-solvents. The ink was applied to the cotton fabric by printing method. The structure, electrical and functional properties of fabrics were investigated. The increase in electrical conductivity was found as a result of the phase separation between PEDOT and PSS due to the use of cosolvents. SEM micrographs showed good adhesion of the ink to the cotton fiber, which was confirmed by the FTIR method. The developed ink has great application potential, especially in electronic devices for biomedical purposes